2017
DOI: 10.1523/jneurosci.2773-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

HDAC7 Ubiquitination by the E3 Ligase CBX4 Is Involved in Contextual Fear Conditioning Memory Formation

Abstract: Histone acetylation, an epigenetic modification, plays an important role in long-term memory formation. Recently, histone deacetylase (HDAC) inhibitors were demonstrated to promote memory formation, which raises the intriguing possibility that they may be used to rescue memory deficits. However, additional research is necessary to clarify the roles of individual HDACs in memory. In this study, we demonstrated that HDAC7, within the dorsal hippocampus of C57BL6J mice, had a late and persistent decrease after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…This was quickly translated to rodents, where numerous studies show that learning induces histone acetylation [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] and the manipulation of histone acetylation can alter memory. Specifically, genetic or pharmacological manipulation of HDACs/HATs have generally established that increasing histone acetylation enhances memory, whereas decreasing histone acetylation impairs memory [ 107 , 109 , 111 , 112 , 113 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: A Brief Review Of Epigenetic Modificationsmentioning
confidence: 99%
“…This was quickly translated to rodents, where numerous studies show that learning induces histone acetylation [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] and the manipulation of histone acetylation can alter memory. Specifically, genetic or pharmacological manipulation of HDACs/HATs have generally established that increasing histone acetylation enhances memory, whereas decreasing histone acetylation impairs memory [ 107 , 109 , 111 , 112 , 113 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: A Brief Review Of Epigenetic Modificationsmentioning
confidence: 99%
“…Among class IIa, HDAC7 is of particular interest given that a single‐dose of modafinil specifically increased H3ac and decreased H4ac at the Hdac7 promoter and increased Hdac7 mRNA levels. HDAC7 seems to play a role in hippocampus‐dependent memory formation and is involved in neuronal protection against apoptotic mechanisms . Interestingly, we and others have shown that modafinil has anti‐oxidative, anti‐inflammatory, and neuroprotective effects on the dopaminergic system .…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the expression of Kelch-like ECH-associated protein 1 (Keap1), the negative regulator of Nrf2, was not changed by 7-HC treatment both in control and colistin conditions ( Supplementary Figure 2), which means that 7-HC could activate Nrf2 signaling via Keap1-independent mechanism. Histone acetylation modification, regulated by HDAC, is an important mechanism for gene transcription regulation (Wang et al, 2014;Jing et al, 2017). Increasing evidences have emphasized the importance of HDAC-regulated epigenetic modification in the development of kidney injury (Wang et al, 2014;Ma et al, 2017;Yoshikazu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation modification, regulated by HDAC, is an important mechanism for gene transcription regulation ( Wang et al, 2014 ; Jing et al, 2017 ). Increasing evidences have emphasized the importance of HDAC-regulated epigenetic modification in the development of kidney injury ( Wang et al, 2014 ; Ma et al, 2017 ; Yoshikazu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%